The Functional Role of Interface Tissue Engineering in Annulus Fibrosus Repair: Bridging Mechanisms of Hydrogel Integration with Regenerative Outcomes - DiStefano, Tyler J. (ACS Biomater Sci Eng, 2020)
Hydrogels are extraordinarily versatile by design and can enhance repair in diseased and injured musculoskeletal tissues. Biological fixation of these constructs is a significant determinant factor that is critical to the clinical success and functionality of regenerative technologies for musculoskeletal repair. In the context of an intervertebral disc (IVD) herniation, nucleus pulposus tissue protrudes through the ruptured annulus fibrosus (AF), consequentially impinging on spinal nerve roots and causing debilitating pain. Discectomy is the surgical standard of care to treat symptomatic herniation; however these procedures do not repair AF defects, and these lesions are a significant risk factor for recurrent herniation. Advances in tissue engineering utilize adhesive hydrogels as AF sealants; however these repair strategies have yet to progress beyond preclinical animal models because these biomaterials are often plagued by poor integration with AF tissue and lead to large variability in repair outcomes. These critical barriers to translation motivate this article to review the material composition of hydrogels that have been evaluated in situ for AF repair, proposed mechanisms of how these biomaterials interface with AF tissue, and their functional outcomes after treatment in order to inform the development of new hydrogels for AF repair. In this systematic review, we identify 18 hydrogel formulations evaluated for AF repair, all of which demonstrate large heterogeneity in their interfacing mechanisms and reported outcome measures to assess the effectiveness of repair. Hydrogels that covalently bond to AF tissue were found to be the most successful in improving IVD biomechanical properties from the injured state, but none were able to restore properties to the intact state suggesting that new repair strategies with innovative surface chemistries are an important future direction. We additionally review biomechanical evaluation methods and recommend standardization in the field of AF tissue engineering to establish mechanical benchmarks for translation and ensure clinical feasibility.